The effects of taxes, regulation, earnings, and organizational form on life insurers' investment portfolio realizations - Collins, Julie H.; Geisler, Greg G.; Shackelford, Douglas A. (Journal of Accounting and Economics, 1997)
We exploit a unique experimental setting within the life insurance industry to examine the effects of taxes, regulation, earnings, and organizational form on life insurers' investment portfolio realizations. A unique equity tax levied on mutual life insurers, as well as the statutory rate variation that occurred during our sample period, allow us to disentangle the effects of taxes from earnings or profitability. Consistent with some policymakers' claims, we find mutual insurers' capital gain realizations are affected by company-specific equity tax rate variation. In addition, we find capital regulation and earnings considerations affect both stocks' and mutuals' realizations.